Optimization of the extraction condition for benzyl isothiocyanate contents in Salvadora persica roots "Siwak" - Maged S. Abdel-Kader; Prawez Alam; Y.T. Kamal; Khalid M. Alkharfy; Ahmed I. Foudah; Saleh I. Alqasoumi (Elsevier, 2019)
Benzyl isothocyanate is the major active antibacterial metabolite in Salvadora persica roots "Siwak" beside two minor isothiocyanate derivatives namely; 3-methoxy benzyl isothiocyanate and 3-hydroxy benzyl isothiocyanate. The extraction condition effect on the amount of benzyl isothiocyanate was explored in detailed study. Both cold and hot extraction with different solvents was applied. The amount of benzyl isothiocyanate was estimated using HPLC and HPTLC. The results indicated that cold extraction of the fresh samples with chloroform offers the maximum amount of benzyl isothiocyanate. Drying process leads to great loss of the active component of Siwak. Keywords: Salvadora persica, Benzyl isothiocyanate, Soxhlet, HPLC, HPTLC